Is There No Honour among the Maltese?: Paradigms of Honour in a Mediterranean Moral Economy. Issue 1 (1st June 2019) - Baldacchino, Jean-Paul
Abstract : The 'honour-shame syndrome' is an anthropological model originally developed in the sixties to describe Mediterranean cultural unity. The model came under heavy criticism, producing a veritable 'anti-Mediterraneanist' backlash. There is, however, a renewed interest in the regional paradigm. This article attempts an analysis of concepts of 'honour' in Malta, contextualising it within the broader ethnographic and linguistic evidence from the region. The author argues that 'honour' is a salient moral concept, and in fact, Maltese has a rich and highly nuanced discourse of honour, which includes both sexualised and nonsexualised aspects. While the author criticises the simplistic 'honour-shame syndrome' paradigm, he argues that honour needs to be considered in its own right as an important key to analysing the contemporary Maltese moral economy as it engages with 'modernity'.